Connecting Public Health Students to Rural and Underserved Areas: Promoting Health Equity Through Field Placement Experiences. Issue 4 (July 2020) - Fifolt, Matthew; McCormick, Lisa C.; Carvalho, Michelle; Lloyd, Laura; Alperin, Melissa
There is an increasing demand for public health workers due to the unmet needs of the poor and underserved populations. However, through field placement experiences, students can actively engage in their own learning while also addressing critical needs of rural and medically underserved populations. In this mixed-methods evaluation, we explored experiences of emerging public health practitioners who participated in the Region IV Public Health Training Center's Pathways to Practice Scholars program between 2014 and 2018. Based on student confidence level ratings and descriptions of field placement experiences, scholars participated in meaningful and enriching field placement experiences in rural areas or on behalf of medically underserved populations. Across all eight Council on Linkages Core Competency Domains, students recorded increased pre- to post-confidence scores, and for many, the field placement experience appeared to affirm their interest in addressing the needs of these communities in the future.